INTEGRATED ASSESSMENT OF RISK FACTORS FOR THE FORMATION OF SOLID DEPENDENCE - Ashurov , Z.Sh; Hayredinova , I.I.; Yadgarova , N.F.; Lyan , E.M. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2023)
The article presents the identified clinical and dynamic features of the formation of polydependence and a complex of risk factors predisposing in the formation of polyaddiction, which made it possible to develop a matrix for the integral assessment of risk factors for the development of polydrug addiction. The prognostic matrix includes all the factors selected for forecasting with their gradation and the values of the integrated risk indicator from the strength of the influence of an individual factor, the relative risk indicator for each factor and their sum for a complex of factors, as well as the normalizing value - the average frequency indicator according to the entire study. the possible range of risk values for the complex of taken factors is derived.